Efectividad de un programa de estimulación del lenguaje sobre la capacidad de solución de problemas de niños de seis años escolarizados (2014)
ABSTRACT: The present study summarizes the description of sexual dimorphism found on metric characteristics in a contemporary sample of skeletons. The burial individual record had data on sex, age, cause of death and birthplace. The metric information corresponding to 44 skull variables, jaw and long bones (humerus, fémur and tibia) was recorded on each subject. The sample consisted of 70 mature individuals of known sex (20 women and 50 males) from a cemetery of the city of Medellín, Colombia. When the statistical comparison between sexes was performed by means of a one-way F test only six of the studied variables were not significant (p > 0.05) to determine sex. In accord with these results, hierarchical list of variables for sex determination aim is proposed. Moreover, it has been conducted a discriminant analysis in order to obtaining prediction equations for sex. Tibia variables yield the highest total percentage of correct classification. They achieved also a higher classification percentage in men that in women, as it is in the qualitative analysis.This study aimed to establish the effectiveness of a language stimulation program on the problem solving ability in children of six years at school. The sample consisted of 22 children (12 girls and 10 boys) from a college in eastern Antioquia (Colombia). The design was quasi-experimental ABA case control with Pre-test and post-test. The group of “cases” was exposed to 10 sessions of language stimulation for a period of five weeks. Intragroup analysis shows that although there is no difference with the reasoning used (valid and erroneous movements), children-case study solve the problem situation in less time than the control children after going through the language stimulation sessions. The intergroup analysis shows no significant differences, probably due to the short time of exposure of children to the program.